A ring of endless light - L'Engle, Madeleine (New York, N.Y. : Dell, 1981)
During the summer her grandfather is dying of leukemia and death seems all around, 15-year-old Vicky finds comfort with the pod of dolphins with whom she has been doing research
Original ed.: New York : Farrar, Straus, Giroux, 1980
Keywords: Death -- Fiction; Dolphins -- Fiction